Chinese Medicine Shensongyangxin Is Effective for Patients with Bradycardia: Results of a Randomized, Double-Blind, Placebo-Controlled Multicenter Trial. (16th January 2014) - Liu, Yunfang; Li, Ning; Jia, Zhenhua; Lu, Feng; Pu, Jielin
Abstract : To evaluate the efficacy and safety of Shensong Yangxin (SSYX) in patients with bradycardia arrhythmias, a randomized, double-blind, and placebo-controlled study was conducted. Patients with bradycardia were randomly assigned to receive either SSYX (trial group, n = 115 ) or placebo (control group, n = 104 ) for 4 weeks. ECG, 24-hour continuous ECG recording, echocardiography, and hepatic and renal function were evaluated at baseline and after treatment. Results showed that the average heart rate, the fastest heart rate, and the lowest heart rate in the trial group were all significantly higher than those in the control group at the end of treatment (P < 0.05 or 0.01, resp.). Compared with pretreatment, the average heart rate, the fastest heart rate, and the lowest heart rate in the trial group all increased significantly after treatment (P < 0.05 or 0.01, resp.). Both the efficacy and the symptom scores in the trial group were significantly better than those in the control group after treatment (both having P < 0.0 1 ). No severe adverse effects were reported. In conclusion, SSYX treatment significantly increased the heart rate in patients with bradycardia without severe side effects. The exact mechanisms remain to be further explored.